Effect of bead milling on chemical and physical characteristics of activated carbons pulverized to superfine sizes. (1st February 2016) - Partlan, Erin; Davis, Kathleen; Ren, Yiran; Apul, Onur Guven; Mefford, O. Thompson; Karanfil, Tanju; Ladner, David A.
Abstract: Superfine powdered activated carbon (S-PAC) is an adsorbent material with particle size between roughly 0.1–1 μm. This is about an order of magnitude smaller than conventional powdered activated carbon (PAC), typically 10–50 μm. S-PAC has been shown to outperform PAC for adsorption of various drinking water contaminants. However, variation in S-PAC production methods and limited material characterization in prior studies lead to questions of how S-PAC characteristics deviate from that of its parent PAC. In this study, a wet mill filled with 0.3–0.5 mm yttrium-stabilized zirconium oxide grinding beads was used to produce S-PAC from seven commercially available activated carbons of various source materials, including two coal types, coconut shell, and wood. Particle sizes were varied by changing the milling time, keeping mill power, batch volume, and recirculation rate constant. As expected, mean particle size decreased with longer milling. A lignite coal-based carbon had the smallest mean particle diameter at 169 nm, while the wood-based carbon had the largest at 440 nm. The wood and coconut-shell based carbons had the highest resistance to milling. Specific surface area and pore volume distributions were generally unchanged with increased milling time. Changes in the point of zero charge (pHPZC ) and oxygen content of the milled carbons were found to correlate with an increasing specific external surface area. However, the isoelectric point (pHIEP ), which measures only external surfaces, was unchanged with milling and also much lower in value than pHPZC . It is likely that the outer surface is easily oxidized while internal surfaces remain largely unchanged, which results in a lower average pH as measured by pHPZC . Graphical abstract: Highlights: Activated carbons were pulverized in a bead mill with varied duration. Ability of activated carbon to reduce in size relates to the precursor material. Milling led to external surface oxidation and a decreased average pH. Pore volume and surface area did not change deterministically with milling. Increased S-PAC material reporting will lead to improved performance characterization.